2017
DOI: 10.1084/jem.20160933
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome assembly is regulated by phosphorylation of the pyrin domain

Abstract: NLRP3 is an innate immune receptor that needs to be tightly regulated to prevent overshooting immune responses. Stutz et al. demonstrate that NLRP3 is phosphorylated as a safeguard against accidental activation, and that dephosphorylation involving PP2A activity is required for NLRP3 activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
272
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 280 publications
(284 citation statements)
references
References 38 publications
9
272
1
2
Order By: Relevance
“…Thus, Stutz et al and Mortimer et al reported that dephosphorylation of serine (S5 or S295) is necessary for NLRP3 activation, whereas Spalinger et al reported that dephosphorylation of a tyrosine (Y861) has this function (13,38,39). It was therefore logical to assume that CARD8 regulates NLRP3 inflammasome by affecting NLRP3 dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Stutz et al and Mortimer et al reported that dephosphorylation of serine (S5 or S295) is necessary for NLRP3 activation, whereas Spalinger et al reported that dephosphorylation of a tyrosine (Y861) has this function (13,38,39). It was therefore logical to assume that CARD8 regulates NLRP3 inflammasome by affecting NLRP3 dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular pathway that connects NLRP3 activation with osmotic pressure differentials involves the activation of pressure sensitive membrane bound calcium channels such as TRPM7 and TRPV2, which promote the influx of calcium (Nilius and Owsianik, 2011; Yaron et al, 2015). The influx of calcium, which can also be induced in microglia following stimulation of the Gα q protein-coupled receptors CASR (Lee et al, 2012) and GPCR6A (Rossol et al, 2012) by the extracellular DAMP calcium, potently activates the NLRP3 inflammasome complex in a process that potentially involves decreasing the intracellular concentration of cAMP (Lee et al, 2012), regulating the enzymatic activity of NLRP3 related calcium-dependent kinases and phosphatases (Ahn et al, 2007; Stutz et al, 2017), or by causing mitochondrial buffering of cytosolic calcium and the formation of ROS by disturbances in the mitochondrial membrane potential (Baughman et al, 2011; Murakami et al, 2012). …”
Section: Priming and Activation Of The Nlrp3 Inflammasomementioning
confidence: 99%
“…L'assemblage de l'inflammasome nécessite également la déphosphorylation de la sérine S5 du domaine PYD, qui permet le recrutement d'ASC. Cette déphosphorylation pourrait être réalisée par PP2A (protein phosphatase 2 A) mais savoir si elle se produit lors du priming ou lors de l'activation n'est pas défini [41] …”
Section: Modifications Post-traductionnelles De L'inflammasome Nlrp3unclassified